Enhancing EFL Reading Comprehension and Engagement through Multimodal Instructional Design: A Convergent Mixed-Methods Study - Riansih, Rismar; Arsyad, Safnil; Adnan, Zifirdaus (Jurnal Pendidikan Progresif, 2025)
Enhancing EFL Reading Comprehension and Engagement through Multimodal Instructional Design: A Convergent Mixed-Methods Study. Objectives: This study explores to what extent the multimodal features incorporated into Indonesian high school English textbooks impact students’ engagement and comprehension during reading. As students engage more and more with visually oriented, digitally mediated texts, it becomes imperative to understand how multimodal materials can shape learning. Method:  "A convergent parallel mixed-method research design was employed. A total of 75 government-issued English course Grade XII students participated in the study. The researchers collected quantitative data through pre-tests, post-tests, and a student engagement questionnaire that measures behavioral, emotional, and cognitive engagement. Qualitative data were collected from an open-ended questionnaire that investigated how participants interpreted the textbooks’ images, colors, layout, and other multimodal resources. Findings: The results indicated that students’ comprehension was significantly improved by multimodal texts, as evidenced by their mean scores compared to traditional texts-only. The students noted that graphic aids assisted their comprehension of difficult language by reinforcing meaning and information recall. The conjunction of multimodal features enhanced motivation and reduced boredom, leading to greater emotional engagement. The qualitative answers also suggested that students found the multimodal layouts more aesthetically appealing, more organized and easier to move along with during a positive reading experience. In summary, the combination of quantitative and qualitative findings shows that multimodal features do significantly contribute to improving students’ engagement and understanding. Conclusion: The findings suggest that English teachers in Indonesia should incorporate a more systematic use of multimodal design in their integration of visual and spatial aspects and help their students question images critically. Multimodal literacy should be embedded in teachers’ pedagogy to create education that is more relevant, inclusive, and effective in today’s EFL classrooms. Keywords: multimodal texts, english textbooks, student engagement, reading comprehension,  EFL.